Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 01s - Saint-Simon, Louis de Rouvroy, duc de, 1675-1755 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 01" by Saint-Simon is a historical account written in the early 18th century. The text offers an intimate and detailed glimpse into the intrigues, personal lives, and social dynamics of the French court during the reign of Louis XIV and the subsequent Regency period. It revolves around the author$1 (Bs experiences and reflections, including his own early life, military aspirations, and relationships with those at court, all set against the backdrop of significant historical events. At the start of the memoir, the author recounts his birth into nobility, highlighting his family background and the influence of his parents, particularly his mother$1 (Bs guidance on personal value and ambition. He reveals his longing to join the military, detailing his entry into the Musketeers and annotating his experiences during campaigns, including the siege of Namur. The narrative further unfolds to include personal anecdotes about those in power, the marriages within the royal family, and the impact of social whims on court life, leading to a rich tapestry of courtly intrigue and a critical examination of prominent historical figures. (This is an automatically generated summary.)s
Release date is 2004-12-03
Produced by David Widger
Keywords: France -- Court and courtiers; France -- History -- Louis XIV, 1643-1715; France -- History -- Regency, 1715-1723